O Pewnym Włóknistym Modelu Gęstego Rusztu - Wilmański, K. (Engineering Transactions, 1966)
This a discussion of a non-giroscopic fibrous plate treated as a continuous model of a dense plane grate. The form of rigidity affinors is analysed in this case together with some particular cases if the body shows locally symmetric elasticity. Particular emphasis is laid on the analogy between the equation of deflection of the fibrous plate and the corresponding equation for an anisotropic plate. A method is devised enabling the solutions obtained to be used for the computation of forces in discrete systems.